University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 4 - Practice Exercises - Page 279: 122



Work Step by Step

Calculate the anti-derivative. Now, $y=\int (x+\dfrac{1}{x})^2 dx=\int (x^2+x^{-2}+2) dx$ We know that $\int x^{n} dx=\dfrac{x^{n+1}}{n+1}+C$ and where $C$ is a constant of proportionality. Thus, $y=\dfrac{x^{2+1}}{2+1}+\dfrac{x^{-2+1}}{-2+1}+2+C=\dfrac{x^3}{3}-\dfrac{1}{x}+2x+C$ Here, $y(1)=1 \implies C=-\dfrac{1}{3}$ Hence, $y=\dfrac{x^3}{3}-\dfrac{1}{x}+2x-\dfrac{1}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.